1988
DOI: 10.1093/infdis/158.4.681
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Diagnosis of Tuberculous Meningitis by Using an Enzyme-Linked Immunosorbent Assay to Detect Mycobacterial Antigen and Antibody in Cerebrospinal Fluid

Abstract: Rapid diagnostic tests for tuberculous meningitis are urgently needed because delayed treatment increases the already high mortality rate of this disease. Direct acid-fast staining of cerebrospinal fluid is the only quick method generally available, but it lacks sensitivity. Therefore, we evaluated the use of an enzyme-linked immunosorbent assay (ELISA) to mycobacterial antigen and antibody in the cerebrospinal fluid of 29 patients with proven tuberculous meningitis, 83 patients with nontuberculous central ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 19 publications
0
31
0
1
Order By: Relevance
“…Antibody detection. While the detection of antibodies in the CSF to diagnose TBM is rapid, earlier studies evaluating the utility of measuring M. tuberculosis-specific antibodies in the CSF have shown that these techniques are limited by the inability to differentiate acute infection from previous infection and problems with cross-reactivity (91, 94) in addition to variable and often poor sensitivity and specificity (13,33,130,149,159,239) (Table 3). An example of a more recent study shows that measuring antibodies against a 30-kDa protein that is a specific antigen of M. tuberculosis (88) yielded a more promising sensitivity of 92% (89).…”
Section: Molecular and Biochemical Analysismentioning
confidence: 99%
“…Antibody detection. While the detection of antibodies in the CSF to diagnose TBM is rapid, earlier studies evaluating the utility of measuring M. tuberculosis-specific antibodies in the CSF have shown that these techniques are limited by the inability to differentiate acute infection from previous infection and problems with cross-reactivity (91, 94) in addition to variable and often poor sensitivity and specificity (13,33,130,149,159,239) (Table 3). An example of a more recent study shows that measuring antibodies against a 30-kDa protein that is a specific antigen of M. tuberculosis (88) yielded a more promising sensitivity of 92% (89).…”
Section: Molecular and Biochemical Analysismentioning
confidence: 99%
“…Two additional groups have reported the detection of specific IgM antibodies in the CSF of patients with tuberculous meningitis, but their data were integrated with results of assays for IgG (5,32).…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of Mycobacterium tuberculosis' in CSF by a culture technique is not only a time-consuming process but also lacks sensitivity. The development of EIA techniques (1)(2)(3)(4)(5) as an aid in the diagnosis of TBM has evoked considerable interest during the past decade. However, interpretation of the results and reliability of the EIAs have been affected by variability in the amount of antigen absorbed onto the surface of individual wells in the polystyrene or polyvinylchloride microtitre plates (6, 7).…”
Section: Rapid Diagnosis Of Tuberculous Meningitis With a Dot Enzyme mentioning
confidence: 99%